IDENTIFIKASI DAERAH RAWAN BANJIR LAHAR PADA KALI WORO DENGAN APLIKASI PROGRAM SIMLAR V.1.0 - Setiono Setiono; Siti Qomariah; Setiono Setiono (Program Studi Teknik Sipil FT UNS, 2014)
Disaster due to debris flow commonly called sediment disaster, SIMLAR V.1.0 application for simulation debris flow 2D toestimate flood Lava prone areas volcano in order development of early warning system, so will reduce negative impact of disaster. Thepurpose of this study is : (1) can identify the type of morphology based rosgen's method.(2)to determine the effectiveness the buildingsabo in conducting debris flow in order development of early warning system(3)to mapped the flood lava prone areas in DAS Woro inthe orderly development of early warning system. This research using secondary data, the secondary data obtained from relevantagencies, the research using the daily rainfall data, the discharge of DAS woro event in 2010. Rain results using Gama I methods,digital elevation model (DEM) was taken in 2011, lava flood prone map from BPPTK. Effective rainfall, digital elevation modeland sediment coefficient input tp the simlar applicaton for further do simulation test. From the simlar application will produce 2Dmap and describe the region lava flood pronein in DAS woro with water volume and sediment volume, the result this research thatflood prone lava areas is a village sukorini areas